Alternative monomer for BisGMA-free resin composites formulations. Issue 7 (July 2020) - Fugolin, Ana P.; de Paula, Andreia B.; Dobson, Adam; Huynh, Vincent; Consani, Rafael; Ferracane, Jack L.; Pfeifer, Carmem S.
Abstract: Objective: Water sorption, high volumetric shrinkage, polymerization stress, and potential estrogenic effects triggered by leached compounds are some of the major concerns related to BisGMA-TEGDMA co-monomer systems used in dental composites. These deficiencies call for the development of alternative organic matrices in order to maximize the clinical lifespan of resin composite dental restorations. This study proposes BisGMA-free systems based on the combination of UDMA and a newly synthesized diurethane dimethacrylate, and evaluates key mechanical and physical properties of the resulting materials. Methods: 2EMATE-BDI (2-hydroxy-1-ethyl methacrylate) was synthesized by the reaction between 2-hydroxy-1-ethyl methacrylate with a difunctional isocyanate (1.3-bis (1- isocyanato-1-methylethylbenzene) – BDI). The compound was copolymerized with UDMA (urethane dimethacrylate) at 40 and 60 wt%. UDMA copolymerizations with 40 and 60 wt% TEGDMA (triethylene glycol dimethacrylate) were tested as controls, as well as a formulation based in BisGMA (bisphenol A-glycidyl methacrylate)-TEGDMA 60:40% (BT). The organic matrices were made polymerizable by the addition of DMPA (2.2-dimethoxyphenoxy acetophenone) and DPI-PF6 (diphenyliodonium hexafluorophosphate) at 0.2 and 0.4 wt%, respectively. Formulations were tested as composite with the addition of 70 wt% inorganic content consisting of barium borosilicate glass (0.7 μm) and fumed silica mixed in 95 and 5 wt%, respectively. All photocuring procedures were carried out by a mercury arc lamp filtered to 320–500 nm at 800 mW/cm 2 . The experimental resin composites were tested for kinetics of polymerization and polymerization stress in real time. Flexural strength, elastic modulus, water sorption, and solubility were assessed according to ISO 4049 . Biofilm formation was analyzed after 24 h by luciferase assay. Data were statistically analyzed by one-way ANOVA and Tukey's test ( α ≤ 0.05). Results: In general, the addition of 2EMATE-BDI into the formulations decreased the maximum rate of polymerization (RPMAX ), the degree of conversion at RPMAX (DC at RPMAX ), and the final degree of conversion (final DC). However, these reductions did not compromise mechanical properties, which were comparable to the BT controls, especially after 7-day water incubation. The incorporation of 60 wt% 2EMATE-BDI reduced water sorption of the composite. 2EMATE-BDI containing formulations showed reduction in polymerization stress of 30% and 50% in comparison to BT control and TEGDMA copolymerizations, respectively. Biofilm formation was similar among the tested groups. Significance: The use of the newly synthesized diurethane dimethacrylate as co-monomer in dental resin composite formulations seems to be a promising option to develop polymers with low-shrinkage and potentially decreased water degradation.